2019
DOI: 10.1002/pds.4799
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant continuation in pregnancy and risk of gestational diabetes

Abstract: Purpose Previous studies observed modestly higher risk of gestational diabetes (GDM) associated with antidepressant use in pregnancy, potentially due to confounding by indication. We assessed the association of antidepressant continuation in pregnancy with GDM, as well as blood glucose levels, after accounting for confounding. Methods We conducted a retrospective cohort study of singleton live births from 2001 to 2014 to women enrolled in Kaiser Permanente Washington, an integrated health care delivery system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Our findings are generally in line with those by Wartko et al, 17 where antidepressant-exposed women were compared to unexposed having an underlying indication for treatment with antidepressants in pregnancy, limiting the risk of indication bias. 15 Maternal depression in pregnancy has also been found to be associated with gestational diabetes, 16 for instance by triggering oxidative stress, chronic inflammation, and insulin resistance, 42 and thus disentangling the effect of medication exposure from that of the underlying maternal disease is crucial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are generally in line with those by Wartko et al, 17 where antidepressant-exposed women were compared to unexposed having an underlying indication for treatment with antidepressants in pregnancy, limiting the risk of indication bias. 15 Maternal depression in pregnancy has also been found to be associated with gestational diabetes, 16 for instance by triggering oxidative stress, chronic inflammation, and insulin resistance, 42 and thus disentangling the effect of medication exposure from that of the underlying maternal disease is crucial.…”
Section: Discussionsupporting
confidence: 91%
“…This comparison raises however concerns of confounding by indication. 15,16 Two additional studies 17,18 could not replicate these findings for the whole antidepressant group when using as comparator women with depression, albeit the GDM risk was elevated after use of venlafaxine, amitriptyline, or sertraline. 17,18 Although studies in non-pregnant subjects have shown that the risk of T2DM increases following the use of antidepressants with greater affinity to the H 1 receptor, 7,12 this research question has not been systematically studied in the context of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and findings of the reviewed studies are summarized in Table 1. Three records were eligible for inclusion in the systematic review, consisting of 1 case-control (Dandjinou et al, 2019), 1 prospective cohort (Lupattelli et al, 2021), and 1 retrospective cohort study (Wartko et al, 2019). They were published from 2011 to 2020, with 1 from Canada, 2 from the United States of America, and 1 from Norway.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In total, 241,845 women were included in the studies of which 12,583 were exposed to antidepressants during pregnancy. None of the studies reported the antidepressant exposure trimester (Dandjinou et al, 2019;Lupattelli et al, 2021;Wartko et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation